CATCHES OF TUNAS AND TUNA LIKE FISHES, IN THE LONGLINE FISHERY AREAS OFF THE COAST OF BRAZIL - Paiva, Melquíades Pinto; Yves Le Gall, Jean (Arquivos de Ciências do Mar, 2018)
In this paper we try to estimate the annual catches of tunas and tuna like fishes in the longline fishery areas off the coast of Brazil, during the years 1956/1971. These areas comprise tropical and South temperate waters, in the Western part of the Atlantic Ocean.